Chandra: A Biography of S Chandrasekhar - Kameshwar C Wali; WALI (Kameshwar C) (New Delhi Penguin Books, 1991)
Chandra is an intimate portrait of a highly private and brilliant man, Subrahmanyan Chandrasekhar, a Nobel laureate in physics who has been a major contributor to the theories of white dwarfs and black holes. "Wali has given us a magnificent portrait of Chandra, full of life and color, with a deep understanding of the three cultures--Indian, British, and American--in which Chandra was successively immersed...I wish I had the job of reviewing this book for the New York Times rather than for Physics Today. If the book is only read by physicists, then Wali's devoted labors were in vain."--Freeman Dyson, Physics Today "An enthralling human document."--William McCrea, Times Higher Education Supplement "A dramatic, exuberant biography of one of the century's great scientists".
Keywords: Biography; Astrophysicist; Chandrashekar nobel physicist